Analisis Tingkat Kesehatan Bank dengan Menggunakan Metode CAMELS pada PT. Bank Pembangunan Daerah Jambi Periode 2015-2019 - Ellys Agustina; Panji Jiblathar (Department of Mathematics, Faculty of Science and Technology Universitas Jambi, 2023)
The structured and integrated management of economic resources has a significant impact on a nation's economic growth. Banks, as crucial financial institutions, play a pivotal role in the stewardship of these economic resources. This article delves into an analysis of the banking health level using the CAMELS method for PT. Bank Pembangunan Daerah Jambi during the period from 2015 to 2019. The CAMELS method is employed to evaluate the bank's health across various indicators, encompassing Capital, Asset Quality, Management, Earnings, Liquidity, and Sensitivity to Market Risk. This assessment holds paramount importance given the micro and macro economics ramifications that banks exert on the economy. The analysis reveals that PT. Bank Pembangunan Daerah Jambi during the aforementioned period falls within the